Constraints on the use and adoption of information and communication technology (ICT) tools and farm machinery by paddy farmers in Nepal - Sigdel, U. P.; Pyakuryal, K. N.; Devkota, D.; Ojha, G. P. (Journal of Agriculture and Forestry University, 2022)
Information and communication technology (ICT) tools such as radio, television, mobile phone, the internet and computers are gaining momentum in Nepal’s agriculture development discourse, filling void that traditional agriculture extension has failed to fill. Agricultural mechanization implies using various power sources and improved farm tools and equipment in agriculture. This study aims to determine the barriers while using ICT tools and agricultural machinery in Jhapa, Kapilbastu and Kailali districts of Nepal. Pretested semi-structured interview schedule was employed to collect data from 390 sample respondents selected randomly. Descriptive statistics and the appropriately developed scales were used in the data analysis. Moreover, respondents considered lack of awareness along with its requirement of skilled human resources and its cost were the primary reasons for the rejection of the use of ICT tools, where the overall rejection level was at a medium level. The constraints level of the use and adoption of farm machinery was found high; the significant constraints considered by the respondents were the high price of the machinery along with poor skills, knowledge, facilities, and poor maintenance service. The overall index value for the rejection of the use and adoption of farm machinery in paddy farming was at a moderate level. The respondents’ primary reasons for the rejection of the use of farm machinery were the high price of the farm machinery long with poor training, poor skilled human resources, and complex ideas to learn. Hence, to overcome to those factors, appropriate awareness campaigns and educational programs are necessary.